Human Dermatoglyphic Traits. Critical Review Of Methods And Ideas. New Trends Of Researches In Poland And In The World. - Budnik, Alicja (Anthropological Review, 1992)
The review was made from the point of view of genetic transmission, source of variability, morphogenesis and functional significance of these traits in men. While pointing the reasons of hitherto failures in solving the primary problems, the difficulties in defining the traits were stressed. The critical review on some dermatoglyphic opinions and new trends of researches in Poland and in the world were presented.